2019
DOI: 10.1002/ppul.24330
|View full text |Cite
|
Sign up to set email alerts
|

Effects of core stabilization exercises on pulmonary function, respiratory muscle strength, and functional capacity in adolescents with substance use disorder: Randomized controlled trial

Abstract: Background: Adolescent substance abuse is a serious and growing problem worldwide.The aim of this study was to investigate the effects of core stabilization exercises on pulmonary function, respiratory muscle strength, and functional capacity in adolescents with substance use disorder (SUD).Methods: This was a prospective randomized controlled trial. A total of 49 adolescent male patients with SUD were randomly assigned to either the exercise group (n = 25; mean age 16.6 years) or the control group (n = 24; me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 39 publications
(63 reference statements)
0
10
0
Order By: Relevance
“…Amăricăi et al [ 22 ] performed 12-week physical therapy (muscle stretching exercise and intensive exercise, breathing training, and core strength training) on mild and moderate AIS patients (Cobb angle of 10–35°), and the results showed that FVC, inspiratory ability, FEV1, expiratory reserve capacity, and 6-minute walking test of AIS patients significantly improved. Moreover, Mustafaoglu et al [ 23 ] found that a 6-week core stability exercise can significantly improve the pulmonary function (FVC, FEV1, and maximum expiratory flow) and respiratory muscle strength (MIP and MEP) of drug abuse adolescents. In this study, AIS patients were given core stability training for 12 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Amăricăi et al [ 22 ] performed 12-week physical therapy (muscle stretching exercise and intensive exercise, breathing training, and core strength training) on mild and moderate AIS patients (Cobb angle of 10–35°), and the results showed that FVC, inspiratory ability, FEV1, expiratory reserve capacity, and 6-minute walking test of AIS patients significantly improved. Moreover, Mustafaoglu et al [ 23 ] found that a 6-week core stability exercise can significantly improve the pulmonary function (FVC, FEV1, and maximum expiratory flow) and respiratory muscle strength (MIP and MEP) of drug abuse adolescents. In this study, AIS patients were given core stability training for 12 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies investigated the effects of core stabilization exercises on respiratory functions in both healthy and patient groups, and it has been shown that it improves respiratory functions and core stabilization in participants (Kim & Lee 2013; Brilla & Kauffman 2014; Cavaggioni et al 2015; Oh & Park 2016; Park & Oh 2017; Mustafaoglu et al 2019; Park & Lee 2019; Park et al 2020). The study by Cavaggioni et al (2015) reported that core stabilization exercises based on breathing and global stretching postures are more effective than traditional abdominal exercises in improving respiratory function and abdominal fitness.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the diaphragm, which is a component of core stability, plays a role in respiration and stabilizing the trunk by controlling intra-abdominal pressure. 3 The "core" is comprised of several groups of muscles including the transversusabdominus, multifidus, diaphragm, and pelvic floor muscles and the diaphragm serves as the roof of the core. 4 From a functional point of view, there are three groups of the respiratory muscles-the diaphragm, the rib cage muscles, and the abdominal muscles.…”
Section: Introductionmentioning
confidence: 99%